Surface sensitivity in scanning transmission x-ray microspectroscopy using secondary electron detection - Hub, Christian; Wenzel, Stephan; Raabe, J.; Ade, Harald; Fink, Rainer (Review of Scientific Instruments, 2010)
The successful integration of electron detection into an existing scanning transmission x-ray microspectroscope (STXM) at the Swiss Light Source is demonstrated. In conventional x-ray detection using a photomultiplier, STXM offers mainly bulk sensitivity combined with high lateral resolution. However, by implementation of a channeltron electron multiplier, the surface sensitivity can be established by the detection of secondary electrons emitted from the sample upon resonant excitation. We describe the experimental setup and discuss several relevant aspects, in particular the schemes to correct for self-absorption in the specimen due to back illumination in case of thicker films. © 2010 American Institute of Physics.